Neurocognition, cerebellar functions and psychiatric features in spinocerebellar ataxia type 34: a case series - Cundari, Maurizio; Kirchhoff, Lena; Vestberg, Susanna; van Westen, Danielle; Dobloug, Sigurd; Markenroth Bloch, Karin; Nilsson, Markus; Wennberg, Linda; Hansson, Boel; Priovoulos, Nikos; Rasmussen, Anders; Gorcenco, Sorina (Frontiers in Computational Neuroscience, 2025)
ObjectiveThis study primarily aimed to comprehensively characterize the neurological, neuroradiological and neurocognitive profiles, as well psychiatric features of individuals with Spinocerebellar Ataxia Type 34 (SCA34) associated with pathogenic variants in the ELOVL4 gene. Secondarily, we investigated the relationship between neurocognitive functions and cerebellar morphology in individuals with SCA34 by correlating structural changes to cognitive performance. Given involvement of the cerebellum in SCA34, our findings will contribute to a broader understanding of the role of the cerebellum in cognition.MethodsFour individuals (52 f, 72 m, 76 m, 76 f) underwent DNA testing using Next-Generation Sequencing and detailed assessment of neurocognitive functions. The test battery evaluated all six cognitive domains: verbal functions, executive functions, attention and processing speed, learning and memory, visuospatial perception and abilities, and social cognition. In addition, cerebellar and motor functions were evaluated using Finger Tapping, Prism Adaptation, and the Motor Speed subtest of the Delis-Kaplan executive function system (D-KEFS). Test results were compared with each individual’s estimated premorbid cognitive level, determined from their highest educational attainment or occupational status prior to disease onset. Psychiatric symptoms related to anxiety, depression, and sleep were reported using clinical scales. The Scale for the Assessment and Rating of Ataxia (SARA) was used to assess ataxia severity. Two individuals and one matched control underwent high-resolution 7T MRI to characterize cerebellar morphology.ResultsNeurocognitive assessments identified cognitive and motor dysfunction across all individuals, including distinct neurocognitive impairments consistent with cerebellar cognitive-affective syndrome (CCAS), along with additional deficits in learning, visual and verbal episodic memory, emotion recognition—a component of social cognition. Anxiety and sleep disturbance, but not depression, were observed in both female participants. High-resolution 7 T MRI revealed structural cerebellar alterations, with moderate to severe bilateral cerebellar atrophy, including the vermis and multiple lobules (Crus II, VIIb, VIIIa, VIIIb, IX), as well as atrophy of the middle and superior cerebellar peduncles, accompanied by mild pontine atrophy. Genetic analyses confirmed the involvement of ELOVL4-related disruptions in long-chain fatty acid biosynthesis, offering insight into the molecular underpinnings of cerebellar degeneration in SCA34.ConclusionIndividuals with SCA34 show cerebellar degeneration accompanied by cognitive, motor, and social-affective impairments consistent with CCAS. Atrophy of the vermis, multiple lobules, and cerebellar peduncles align with these deficits, highlighting the cerebellum’s key role in cognition. ELOVL4-related disruptions in fatty acid biosynthesis provides insight into the molecular basis of SCA34. Together, these findings advance our understanding of how cerebellar pathology contributes to complex neurocognitive and psychiatric symptoms in genetic ataxias.